TRANSCONTINENTAL INTEGRATION AND ELECTRONIC DOCUMENT CIRCULATION IN THE LOGISTICS OF TRANSPORT FLOWS - E. Komarova (Вестник университета, 2017)
The article examines the current state and problems of international logistic, identifies the features of document circulation (paper and electronic) in the process of promoting commodity-material and related flows, and formulates approaches to the creation of an integration information platform in Russia.